MENUMBUHKAN SEMANGAT WIRAUSAHA MENUJU KEMANDIRIAN EKONOMI UMAT BERBASIS PESANTREN (Studi Kasus Di PP Darul Ulum Banyuanyar Pamekasan) - Rudy Hariyanto (NUANSA: Jurnal Penelitian Ilmu Sosial dan Keagamaan Islam, 2017)
Islamic boarding school is currently experiencing a tremendous value shift especially related to the world of work. Nowdays the development of entrepreneurship at schools has become a necessity or need, especially if it is associated with a boarding school education that emphasizes self-reliance, hard work, discipline and honest that support the spirit of entrepreneurship. Islamic boarding school of Darul Ulum Banyuanyar Pamekasan is one of the oldest boarding school in Madura, which has a firm commitment to the development of entrepreneurship among its students. Islamic boarding school of Darul Ulum Banyuanyar have a very big role in creating young entrepreneurs with innovative, independent, and creative as an effort to arouse the economic autonomy of students either at the time they are still at boarding school or later in the midle of society. From the results of this research, it is expected to be a reference and inspiration for other Islamic boarding schools in creating new entrepreneurs and arousing creative economic efforts to set up public economic autonomy The present research uses qualitative descriptive technique. Data collection techniques include observation, interviews and documentation. Respondents in this study are leader and caretaker of Islamic boarding school of Darul Ulum Banyuanyar, business manager who owns Boarding School, students and alumni of the participating students as involved in entrepreneurship at Darul Ulum Islamic boarding school, Banyuanyar. While the secondary data in this study come from the supporting data in the form of books, journals, internet, papers, and literature or libraries that support other research studies. The research result are: 1) Islamic boarding school of Darul Ulum Banyuanyar Pamekasan in fostering the entrepreneurial spirit among its students with vision for bearing Islamic generations that behave well, have applicable knowledge, and act scientifically. In practice, the students are given freedom in doing activities that support the achievement of the vision as long as those provide benefits to himself and others. 2) Creative business is run by the students and alumni of Islamic boarding school of Darul Ulum Banyuanyar Pamekasan including shops, products, services and finance sector. The entrepreneurial activities in the department store include the household segmentation to the local area around the pesantren. Production activities include the production of drinking water in the packaging of Nuri, the production of ice cubes, snack production, and handicraft production. While in the service sector include copying, typing and binding. And the financial activities of the establishment of BMT Nuri which already has 16 branches. 3) Islamic boarding school of Darul Ulum Banyuanyar, Pamekasan educate autonomy in all fields including economic autonomy. The attempts of the students for being autonomous contitute by participating in running a business during becoming students and their own business after diving in the community.